PRODUKSI DAN KANDUNGAN FLAVONOID UMBI TANAMAN BAWANG DAYAK (Eleutherine palmifolia) DENGAN PEMBERIAN NPK 16:16:16 PADA BERBAGAI UMUR PANEN - Rosmawaty, T.; Jumin, Hasan Basri; Mardaleni, Mardaleni; Sinaga, Charles (DINAMIKA PERTANIAN, 2020)
ABSTRACT The objectives of this research are to find out the number of Dayak onion production at various ages of harvest by providing NPK fertilizer 16.16.16. and to find out the content of Flavonoids at various ages with NPK 16:16:16 fertilizer application. The research was conducted at the Experimental Garden of the Islamic University of Riau for 6 months, starting from March to August 2018. The completely randomized design with factorial 3 x 4 was used. Data were analyzed descriptive approach. The parameters observed were the number of clump tubers, per clump dry weight, Simplicia dry weight, flavonoid content, phenolic content, and antioxidant activity. The results showed that the interaction of NPK 16:16: 16 dosages and harvesting age had no effect on the all observed parameters. The best treatment of NPK 16:16:16 2,5 g/plant (N3) for optimum production and 1,25 g/plant (N1) for maximum total flavonoid content. With the best treatment of NPK 16:16:16 2.5 g/plant (N3) for maximum production and 1.25 g/plant (N1) for maximum total flavonoid content. For optimal age and 5 (months) for maximum total flavonoid content.